Do personal traits moderate cognitive abilities in diabetes mellitus? - Mirena P. VALKOVA (Archives of the Balkan Medical Union, 2019)
Introduction. The association between cognitive functions and personal traits is a question of interest and debate. Diabetes mellitus is associated with cognitive changes.